2011
DOI: 10.1080/10875301.2011.595255
|View full text |Cite
|
Sign up to set email alerts
|

Should Chat Reference Be Staffed by Librarians? An Assessment of Chat Reference at an Academic Library Using LibStats

Abstract: This study analyzes 1557 chat reference questions received at Grand Valley State University Libraries over four semesters to determine the quantity and nature of the questions. Results indicated that use of chat reference was low and that less than a quarter of chat questions required a librarian to answer. The cost of a librarian answering a chat question ranged from $37 to $439 per question. The findings suggest that assigning chat reference to trained reference assistants will not affect patron service and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Several studies have argued that relying on professional librarians alone to staff a reference desk or chat service is cost-ineffective (Bracke et al, 2007;Bravender, Lyon, & Molaro, 2011;Ryan, 2008). Case studies have also reported a high proportion of simple directional or technology questions at the reference desk, suggesting that many transactions do not require the skills of a librarian (Bishop & Bartlett, 2013;Ryan, 2008;Stevens, 2013).…”
Section: Appropriateness and Effectiveness Of Student Staffingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have argued that relying on professional librarians alone to staff a reference desk or chat service is cost-ineffective (Bracke et al, 2007;Bravender, Lyon, & Molaro, 2011;Ryan, 2008). Case studies have also reported a high proportion of simple directional or technology questions at the reference desk, suggesting that many transactions do not require the skills of a librarian (Bishop & Bartlett, 2013;Ryan, 2008;Stevens, 2013).…”
Section: Appropriateness and Effectiveness Of Student Staffingmentioning
confidence: 99%
“…However, there are conflicting findings about the most common question types on chat. Bravender et al (2011) and Cabaniss (2015) reported that reference questions accounted for 17.7% and 23.3% of chats on their respective services, leading them to recommend staffing models in which graduate students or reference assistants handle the majority of chats. However, other researchers have reported that complex research or reference questions occur in 40%-66% of chats, supporting staffing by professional librarians (Coté et al, 2016;Fuller & Dryden, 2015;Morais & Sampson, 2010).…”
Section: Appropriateness and Effectiveness Of Student Staffingmentioning
confidence: 99%
“…Some studies, such as the one performed by Bravender et al (2011), indicate that student workers are capable of exhibiting high levels of accuracy as well as effectiveness. The researchers' study analyzed a sample of over 1,500 chat reference questions at Grand Valley State University, using the library statistics program LibStats.…”
Section: Bl 283mentioning
confidence: 99%
“…Bravender, Lyon, and Molaro did a cost analysis of the virtual reference service at a medium-sized liberal arts university with a small percentage of graduate students and concluded that with less than a quarter of questions requiring a librarian to answer, having librarians staff the service was not cost effective. 16 However, other studies suggest that professional librarians' skills are well suited to offering virtual reference service. In their systematic review, Matteson, Salamon, and Brewster assert that "Providing library service via chat technology requires competencies in both communication skills as well as reference skills" and this statement could be interpreted as an endorsement for such a service model.…”
Section: Research Questions Research Sub-questionsmentioning
confidence: 99%